2020
DOI: 10.1109/access.2020.3017458
|View full text |Cite
|
Sign up to set email alerts
|

A Life Cycle-Cost Analysis of Li-ion and Lead-Acid BESSs and Their Actively Hybridized ESSs With Supercapacitors for Islanded Microgrid Applications

Abstract: The combination of supercapacitors (SCs) with Li-ion Batteries (LIBs) and Lead-Acid Batteries (LABs) as hybrid ESSs (HESSs) have widely been proposed for Microgrid (MG) applications. The SCs of HESSs eliminate the stress of surge currents on LIBs and LABs, which increases their life cycles, and decreases their life cycle costs and hence decreases the HESSs operational costs. However, the active topology of HESS, which is the most commonly used configuration, requires an extra SC and an extra DC/DC converter in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 41 publications
0
10
0
1
Order By: Relevance
“…When calculating the cost of energy storage, 27 the whole life cycle is considered, and the method of Net Present Value(NPV) conversion is adopted. The formula is: Cc=C1+i=0n1+rn1r1+rnC2 where C c is the life cycle cost of energy storage.…”
Section: Optimal Allocation Of Classified Mitigationmentioning
confidence: 99%
“…When calculating the cost of energy storage, 27 the whole life cycle is considered, and the method of Net Present Value(NPV) conversion is adopted. The formula is: Cc=C1+i=0n1+rn1r1+rnC2 where C c is the life cycle cost of energy storage.…”
Section: Optimal Allocation Of Classified Mitigationmentioning
confidence: 99%
“…However, the batteries are not high power ESSs, and if they are used for short‐term power regulations, they will suffer from the aging problem, which increases the replacement cost significantly 4 . Therefore, in various studies, it has been proposed to use a high power ESS mostly an SC in parallel with the battery as a hybrid ESS (HESS), which increases the battery lifetime by utilizing SC and battery for short‐term power regulations and long‐term energy management, respectively 7 . In Reference 8, an energy management and coordinated control strategy have been proposed for an islanded AC MG with HESS.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the utilization of PV for PFC becomes efficient as it mostly operates at MPP, and the consumers' discomfort is also avoided as they do not experience long disturbances in residences' light intensity. Proposing to use PVs and SLEDLLs for handling PFC without FTSs in case of failure of SC, its converter or its controller, so that the MG is stabilized even when the SC is not operational. Previous studies like 5,7 have not considered the operational conditions during which the main ESS fails to handle the frequency control. In this paper, the reliable and safe operation of MG is ensured during these conditions using the proposed control scheme. Introducing a novel scheme for fast controlling of TCLs to participate in PFC.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that lithium‐ion battery is more preferable than lead‐acid battery considering the levelized cost of electricity 32 . Torkashvand et al have performed a life cycle cost analysis of lead‐acid and lithium‐ion battery with supercapacitor storage medium for islanded microgrid applications 33 . Li et al performed a techno‐economic study on standalone hybrid diesel generator‐wind‐battery system with different battery technologies (lead‐acid, lithium‐ion, and zinc‐bromine ) .…”
Section: Introductionmentioning
confidence: 99%